2022
DOI: 10.1097/nan.0000000000000481
|View full text |Cite
|
Sign up to set email alerts
|

Changing the Buffer in Buffered Lidocaine

Abstract: Hospitalized patients require venous access for procedures, treatments, or therapies. The use of lidocaine for pain relief during central vascular access device (CVAD) insertion is a standard of practice. Lidocaine buffered with sodium bicarbonate has been shown to provide significantly more pain relief in the sensation of pain upon injection. Shortages of lidocaine with bicarbonate provided an opportunity to explore other options to provide pain relief during CVAD insertion. The PICO question for this project… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Raising the pH of injectable anesthetic, most commonly with sodium bicarbonate, has more consistently been found to significantly decrease pain scores [38 ▪ ,39]. Interestingly, a recent study found that buffering lidocaine with normal saline was equally effective to buffering with sodium bicarbonate [40].…”
Section: Intradermal Anesthesiamentioning
confidence: 99%
“…Raising the pH of injectable anesthetic, most commonly with sodium bicarbonate, has more consistently been found to significantly decrease pain scores [38 ▪ ,39]. Interestingly, a recent study found that buffering lidocaine with normal saline was equally effective to buffering with sodium bicarbonate [40].…”
Section: Intradermal Anesthesiamentioning
confidence: 99%